2004
DOI: 10.1007/s10265-003-0137-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sugar content and activity of vacuolar acid invertase during low-temperature storage of potato tubers from six Japanese cultivars

Abstract: The storage of potato tubers at low temperatures leads to the accumulation of sugars in a process called "low-temperature sweetening." To understand this phenomenon, we measured the sugar contents and the activity of acid invertase over several months in tubers of six Japanese cultivars stored at 4 degrees C or 20 degrees C. At 20 degrees C, few changes in sugar contents took place in any of the tubers. On the other hand, when stored at 4 degrees C, three types of changes were observed among the cultivars: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…The extraction and determination of sugars were carried out as previously described. 23) Frozen tuber slices (about 10 g fresh weight) were homogenized in 80% (v/v) ethanol, and the sugars in the homogenate were extracted at 80 C for 1 h. After centrifugation, the supernatant was dried, dissolved in distilled water, and passed through a membrane filter (0.2 mm Omnipore, Millipore, Tokyo). The concentrations of sugars in the filtrate were determined by HPLC (SC-8020, Tosoh, Tokyo) with a TSKgel Amide-80 column (4:6 Â 250 mm, Tosoh) and an RI detector (RI-8020, Tosoh).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction and determination of sugars were carried out as previously described. 23) Frozen tuber slices (about 10 g fresh weight) were homogenized in 80% (v/v) ethanol, and the sugars in the homogenate were extracted at 80 C for 1 h. After centrifugation, the supernatant was dried, dissolved in distilled water, and passed through a membrane filter (0.2 mm Omnipore, Millipore, Tokyo). The concentrations of sugars in the filtrate were determined by HPLC (SC-8020, Tosoh, Tokyo) with a TSKgel Amide-80 column (4:6 Â 250 mm, Tosoh) and an RI detector (RI-8020, Tosoh).…”
Section: Methodsmentioning
confidence: 99%
“…Previously we reported that there are three types of change in sugar content among cultivars for tubers stored at 4 C: type-1, increased levels of reducing sugars during storage; type-2, a trend similar to that of type-1 but with much lower levels of reducing sugars throughout storage; and type-3, an increase in sucrose but not in reducing sugars. 23) Toyoshiro, Snowden, Irish Cobbler, and Hokkai No. 89 can be classified into type-1.…”
Section: Cultivar Differences In Tuber Components and Their Effects Omentioning
confidence: 99%
“…Some of the Suc produced is transported into the vacuole, where it is hydrolyzed to Glc and Fru (Isla et al, 1998). This step is predominantly controlled by the vacuolar acid invertase (VINV), and there is a strong association between VINV activity and the accumulation of reducing sugars during cold storage (Matsuura-Endo et al, 2004).…”
mentioning
confidence: 99%
“…During the low-temperature storage of Inca-no-mezame tubers, the content of sucrose but not those of reducing sugars continued to rise (Matsuura-Endo et al 2004). In contrast, in the Irish Cobbler tubers, the contents of reducing sugars but not that of sucrose continued to increase during the low-temperature storage (Matsuura-Endo et al 2004). Interestingly, in this experiment, the total reducing sugar content of the Inca-nohitomi tubers after low-temperature storage was higher than that of Inca-no-mezame (4.43 mg/g fresh weight) and similar to that of Irish Cobbler (11.74 mg/g fresh weight) ( Table 5).…”
Section: Breeding Processmentioning
confidence: 93%
“…During the storage at 4°C, the following 3 changes occurred in the sugar contents: (1) the levels of reducing sugars increased during the storage period, (2) the levels of reducing sugars were low throughout the storage period; and (3) the level of sucrose but not those of reducing sugars increased (Matsuura-Endo et al 2004). During the low-temperature storage of Inca-no-mezame tubers, the content of sucrose but not those of reducing sugars continued to rise (Matsuura-Endo et al 2004). In contrast, in the Irish Cobbler tubers, the contents of reducing sugars but not that of sucrose continued to increase during the low-temperature storage (Matsuura-Endo et al 2004).…”
Section: Breeding Processmentioning
confidence: 99%